Soil-geosynthetic interaction in inclined-plane shear and geosynthetic short-term tensile response – Influence of installation damage. (8th March 2021) - Pinho-Lopes, Margarida; Lopes, Maria de Lurdes
Graphical abstract: Highlights: Installation damage caused an increase in the skin friction available. Structure had higher impact on tensile response than on soil-geosynthetic interface. Interface strength without important changes; geotextile's tensile strength reduced. Interface strength: laboratory damage optimistic compared to field installation. Reduction factor for tensile strength conservative to represent interface strength. Abstract: This paper contributes to better understanding how installation damage affects the soil-geosynthetic interaction in inclined plane shear movement and the tensile response of geosynthetics. Installation damage was induced in the field and simulated in laboratory adapting a standardised procedure. Three geosynthetics were studied: one geotextile and two geogrids. The installation damage affected the soil-geosynthetic interface strength and the sliding mechanisms observed. The results showed that installation damage often caused an increase in the skin friction available associated to increased surface roughness, not always apparent from visual inspections. For most samples, the friction mobilised in solid area of the geogrids increased after installation damage, which depended on the geogrid. The reduction factors for installation damage for the inclined plane shear strength and the tensile strength of the geosynthetics were compared. Although the interface shear strength did not change significantly for any of the geosynthetics studied, the tensile strength of the geotextile was severely reduced. The structure of the geosynthetics had a higher impact on their tensile response after damage than on the soil-geosynthetic interface in inclined plane shear. The mechanical damage induced in laboratory underestimated the reduction factor for the interface strength in inclined shear plane movement relative to field installation damage. The results show that the interface shear strength was not significantly influenced by installation damage and that the standardised laboratory test used to induce mechanical damage is able to represent satisfactorily the effect of the installation damage on the inclined plane shear response of soil-geosynthetic interfaces.